Directors’ Compensation, Corporate Attributes, and Firm Performance of Selected Listed Firms in Nigeria: Kompensasi Direktur, Atribut Perusahaan, dan Kinerja Perusahaan pada Perusahaan Terpilih yang Terdaftar di Nigeria. - Ekokotu Ekokotu; Sinebe Sinebe; Eyenubo Eyenubo (Academia Open, 2024)
This study investigates the impact of Directors' Compensation and Corporate Attributes on firms' performance using data from sixty-seven listed firms on the Nigerian Exchange Group (NGX) spanning from 2012 to 2021. Through regression analysis, the research reveals a negative relationship between Director Compensation and firm performance, measured by returns on assets (ROA). Additionally, firm size exhibits a negative association with performance, while firm value positively influences success. Leverage, on the other hand, is found to negatively correlate with firm performance. The study suggests strategic management overhauls in Nigerian firms, emphasizing optimized financial structures, balanced leverage, and prudent debt management to mitigate financial risks and enhance overall performance. Furthermore, aligning Director's compensation with performance metrics is recommended to foster accountability, efficient resource management, and alignment of individual interests with overall corporate objectives. Highlights: Negative ROA Correlation: Directors' Compensation shows a negative relationship with firm performance measured by ROA. Strategic Overhauling Recommendation: Suggests optimizing financial structures and prudent debt management in Nigerian firms. Compensation-Performance Alignment: Advocates aligning Director's compensation with metrics for accountability and efficient resource management. Keywords: Directors' Compensation, Return on Asset, Corporate Attributes, Performance, Firms Size